A history of changing aesthetic values in the Yarra Valley landscape, Victoria. (13th October 2015) - Lennon, Jane L.
Abstract: Aesthetic responses to landscape may be emotional, sensory, or experiential, or a combination; it is a difficult value to identify and assess. This paper considers changing perceptions of the aesthetic values of the Yarra Valley landscape using a heritage methodology that involves examining artistic, creative, and published sources accounting for a lengthy period of changing land use. Scenic quality mapping, where available, is used as a support, and extensive reference is made to Australian impressionist art. Artworks for Yarra Valley landscapes may be considered as being among the cultural heritage indicators of significance and there is a new aesthetic of land art in private venues for the visiting public. The paper also illustrates how aesthetic values have been more broadly recognised in the post‐World War II era and become the domain of planning authorities as well as artists. It is for regional planners to be aware of and maintain these aesthetic values in the landscape.